Novel Gd(OH)3, GdOOH and Gd2O3 Nanorods: Microwave-Assisted Hydrothermal Synthesis and Optical Properties - Almeida,Maciel Salomão de (2016)
We present a study of the controlled synthesis and optical properties of single-crystals Gd(OH)3, GdOOH and Gd2O3 nanorods. In this work, Gd(OH)3 nanorods were synthesized by a simple and fast microwave-assisted hydrothermal method. This process combined with the thermal decomposition oxidation of Gd(OH)3 nanorods as precursors enabled the preparation of single-crystalline GdOOH and Gd2O3 structures with well-defined morphology at low temperatures. The crystal structure dependence on the optical properties was investigated. We observed a green shift effect on the photoluminescence (PL) emission spectra from Gd(OH)3 to Gd2O3 nanorods, which can be attributed to different types of surface defects, as well as intrinsic properties that contribute significantly to the modified PL behavior.